Evaluation of Minnesota Score in the Allocation of Venovenous Extracorporeal Membrane Oxygenation During Resource Scarcity - Jillian K. Wothe; Zachary R. Bergman; Arianna E. Lofrano; Melissa Doucette; Ramiro Saavedra-Romero; Matthew E. Prekker; Elizabeth R. Lusczek; Melissa E. Brunsvold (Critical Care Research and Practice)
Background. In this study, we evaluate the previously reported novel Minnesota Score for association with in-hospital mortality and allocation of venovenous extracorporeal membrane oxygenation in patients with acute respiratory distress syndrome with or without SARS-CoV-2 pneumonia. Methods. This was a retrospective cohort study across four extracorporeal membrane oxygenation centers in Minnesota. Logistic regression was used to assess the relationship between the scores and in-hospital mortality, duration of ECMO cannulation, and discharge disposition. Priority groups were established statistically by maximizing the sum of sensitivity and specificity and compared to the previous qualitatively established priority groups. Results. Of 124 patients included in the study, 38% were treated for COVID-19 acute respiratory distress syndrome. The median age was 48 years, and 73% were male. The in-hospital mortality rate was 38%. The Minnesota Score was significantly associated with in-hospital mortality only (OR 1.13, p=0.02). Statistically determined cut points were similar to qualitative cut points. SARS-CoV-2 status did not change the findings. Conclusions. In our patient cohort, the Minnesota Score is associated with increased mortality. With further validation, proposed priority groups could be utilized for allocation of ECMO in times of increasing scarcity.